2018
DOI: 10.1089/neu.2017.5584
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Stability Enabled by Noninvasive Spinal Electrical Stimulation after Spinal Cord Injury

Abstract: Electrical neuromodulation of spinal networks improves the control of movement of the paralyzed limbs after spinal cord injury (SCI). However, the potential of noninvasive spinal stimulation to facilitate postural trunk control during sitting in humans with SCI has not been investigated. We hypothesized that transcutaneous electrical stimulation of the lumbosacral enlargement can improve trunk posture. Eight participants with non-progressive SCI at C3-T9, American Spinal Injury Association Impairment Scale (AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 78 publications
(103 reference statements)
4
124
1
Order By: Relevance
“…Although recent transcutaneous spinal cord stimulation studies have shown improvement of trunk control during sitting 16 and self‐assisted standing 17 in individuals with SCI, this is the first study to show that tES can facilitate volitional movements in the completely paralyzed leg of a SCI patient after just 16 weeks of stimulation and training. This finding is comparable with previous research using invasive epidural electrical stimulation on a motor complete paraplegic patient regaining volitional movements of lower limbs after stimulation and training 4 .…”
Section: Discussionmentioning
confidence: 71%
“…Although recent transcutaneous spinal cord stimulation studies have shown improvement of trunk control during sitting 16 and self‐assisted standing 17 in individuals with SCI, this is the first study to show that tES can facilitate volitional movements in the completely paralyzed leg of a SCI patient after just 16 weeks of stimulation and training. This finding is comparable with previous research using invasive epidural electrical stimulation on a motor complete paraplegic patient regaining volitional movements of lower limbs after stimulation and training 4 .…”
Section: Discussionmentioning
confidence: 71%
“…Regardless of the exact mechanism, the ratio between tolerance and spinally evoked motor potentials has to be considered when choosing a stimulation paradigm for studies that require TSS‐induced motor activation for functional outcomes (e.g., for standing such as in Sayenko et al, 2019). On the other hand, previous studies have demonstrated the TSS can be used to facilitate other functions such as rhythmic motions (Gerasimenko et al, 2015), trunk stability (Rath et al, 2018), cardiovascular function (Phillips et al, 2018), and bladder function (Gad et al, 2018) in individuals with spinal cord injury, without directly inducing motor responses. These studies used the carrier frequency stimulation paradigm in an attempt to increase stimulation intensity and engage spinal interneural networks while reducing stimulation‐related pain.…”
Section: Discussionmentioning
confidence: 99%
“…As such, mechanisms of spinal neuromodulation may also include activation of spinal interneural networks and antidromic activation of ascending fibers in the dorsal columns. TSS has been used to increase excitability at multiple levels of the spinal neuraxis to enable motor and autonomic functions in individuals with chronic spinal cord injury (SCI) (Gad et al, 2018; Hofstoetter et al, 2013, 2015; Minassian et al, 2013, 2016; Phillips et al, 2018; Rath et al, 2018; Sayenko et al, 2019). Although TSS has been examined as a possible clinical intervention for individuals with SCI, the promising findings with regard to motor recovery and the noninvasive nature of the technique could make TSS suitable for use with other neurologically‐impaired populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to EES which requires a permanently implanted array on the spinal cord requiring a laminectomy, followed by connection to an implanted electrical pulse generator, wearable transcutaneous stimulation systems could be donned and doffed by subjects or their caretakers. Early reports have shown promising results as transcutaneous stimulation has demonstrated efficacy in enabling voluntary control of lower limb movement while side‐lying in five subjects with chronic paraplegia and increased trunk stability in eight individuals with SCI . In addition, transcutaneous stimulation increased grip force by 325% in eight subjects with cervical level injuries after just eight sessions .…”
Section: Alternative Approaches and Strategiesmentioning
confidence: 99%